Museu virtual interativo : perspectivas e possibilidades de apropriação por professores em suas práticas pedagógicas com crianças - Dumbra, Camila Nataly Pinho (2013)
This dissertation focuses the virtualization Abilio Barreto Historical Museum (MHAB) and as main purpose to analyze the possibilities of appropriating MHAB in the virtual environment, by teachers in their teaching practices with children. We seek to understand the phenomenon through research supported by documentary evidentiary paradigm of Ginzburg (1989). The concept was based on virtual Levy (1996), and analyzes about the museum founded in Ramos (2004), in view of building a new understanding of the environment museum and digital environment. We seek to work with the concept of virtual museum and highlight museums as mediators that enable the construction of historical knowledge. Throughout the work, approach to concepts relevant to understanding the rapidly changing society in which we live that determines our actions and our behavior. Moreover, focuses on the theme \"Media and Child\", to reflect on the fundamental object of research. Enters is also in discussions in the field of museums and their relationship with technology. Presents issues raised from the virtual visit to MHAB and approximation between museum and education with a focus on teaching history. Furthermore, analyzes weave themselves about the educational possibilities for learning and historical museum for children. Finally, to address reflections about the possibilities of appropriation for teachers interactive virtual museum visitors. The virtual museums have possibilities as to immediate access, even if it is difficult to access by physical barriers and enables new forms of interaction and, consequently, new ways of learning. In this sense, the teacher can act as a mediator in the relationship museum visitor-expanding vision of belonging Visitor in relation to history, and furthermore bring out perceptions, interpretations and deconstructions of plural meanings constructed and conveyed by the museum. Given these analyzes, the museum presents itself as a space where individuals can be recognized as belonging to their environment by observing the past.